Early inpatient rehabilitation for acutely hospitalized older patients: a systematic review of outcome measures - Heldmann, Patrick; Werner, Christian; Wolf-Belala, Nacera; Bauer, Jürgen M.; Hauer, Klaus (BMC geriatrics, 2019)
Selecting appropriate outcome measures for vulnerable, multimorbid, older patients with acute and chronic impairments poses specific challenges, which may have caused inconsistent findings of previous intervention trials on early inpatient rehabilitation in acutely hospitalized older patients. The aim of this review was to describe primary outcome measures that have been used in randomized controlled trials (RCTs) on early rehabilitation in acutely hospitalized older patients, to analyze their matching, and to evaluate the effects of matching on the main findings of these RCTs.
Gesehen am 02.10.2019